Prevention Acts towards Bullying in Indonesian Schools: A Systematic Review - Wandi Subroto (STAI Hubbulwathan Duri, 2021)
Bullying is quite a common issue in many Indonesian schools. This act of violence, verbally or nonverbally, is often experienced by students; even this is considered normal and often happens. Bullying is a dangerous act because it can damage the mentality of the younger generation, who are the nation's next generation. Therefore, it is necessary to take any action to prevent this, one of which is socialization and legal education to students in schools. As a response to the issue, this study was conducted to file the studies that have been conducted in the cases of bullying among students in Indonesia, both traditional and cyberbullying. This study uses a systematic review as the research design. Data was taken from a popular searching engine, google scholar. Five articles were sorted and chosen as the data. Miles and Huberman’s (1994) framework was utilized to analyze the data. As for presenting stage, the researcher employed Triandis’s (1978) concept of social behaviour comprising attitudes, values, and validation from others. The results showed that cases of bullying among students, in general, were in the form of verbal bullying, social bullying, and physical violence, which were generally caused by the family environment, peers, mass media, and socio-cultural environment. Practical implications and recommendations for future researchers are also presented in this article.